Time-interleaved digitisation systems for time of flight mass spectrometry: a review. (29th October 2021) - Karthic, R.S.; Ragumadhavan, R.; Britto, K.R. Aravind; Vimala, R.; Arivalagan, M.
We consider time-interleaved analogue-to-digital converters (TIADCs) to realise higher sampling rate, high speed systems such as time-of-flight mass spectrometry (ToF-MS). TIADC has inherent offset, gain and timing mismatch errors. Out of these errors, time skew, a function of input signal frequency, degrades system performance and hence the resolution and resolving power of ToF-MS. This paper reviews the various time skew detection and correction mechanisms. We consider analogue, digital, background and foreground based detection and correction methods. Analogue methods are slow and noise prone. Digital background methods use filter banks and are computationally intensive with convergence issues. Input signal statistics based method like blind digital background correction algorithms impose additional constraints like the necessity of wide sense stationary (WSS) and thus require statistical information of the input signal. Digital foreground perfect reconstruction method uses a pilot tone to detect and correct errors. This method is applicable only to narrow bandwidth signal.